IWMI’s vulnerability mapping shapes Sri Lanka’s National Climate Change Adaptation Strategy - CGIAR Research Program on Climate Change, Agriculture and Food Security (2016)
IWMI and its partners, Centre for Poverty Analysis (CEPA) and National Council for Disaster Management, Ministry of Disaster Management and Human Rights, Sri Lanka, conducted a study ‘Impact of Climate Change on Water Resources and Agriculture in Sri Lanka: A Review and Preliminary Vulnerability Mapping’, which significantly influenced Sri Lanka’s climate change strategies and policies. The study, a first of its kind, provided background information and identified research gaps on the impacts of climate change on the agricultural sector and water resources.